Lilly gets left out - Hamilton, Ruth. ([Willow Vale, N.S.W.] : ZealAus Publishing, 2019)
"Lilly and Violet are sisters and best friends. They do everything together until Violet gets a boyfriend. So Lilly decides to make things go back to the way they were. A charming tale about handling change." --External website.
Title from title screen.
For primary age children.
Also available in print.
Mode of Access: Available online.
Keywords: Friendship in children -- Juvenile fiction; Children's stories; Electronic books